2015
DOI: 10.1155/2015/964131
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases in Inflammatory Bowel Disease: An Update

Abstract: Matrix metalloproteinases (MMPs) are known to be upregulated in inflammatory bowel disease (IBD) and other inflammatory conditions, but while their involvement is clear, their role in many settings has yet to be determined. Studies of the involvement of MMPs in IBD since 2006 have revealed an array of immune and stromal cells which release the proteases in response to inflammatory cytokines and growth factors. Through digestion of the extracellular matrix and cleavage of bioactive proteins, a huge diversity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 216 publications
(213 reference statements)
5
126
0
7
Order By: Relevance
“…Several matrix metalloproteinase (Mmp), such as Mmp-2, -3 and -9 are up-regulated in the intestines of IBD patients and may regulate epithelial barrier function [45], [46]. Because the expression of these Mmps are associated with Nox1 and Duox1 [47], [48], [49], we analyzed the gene expression in our mice and found that Mmp-2 and Mmp-9 , but not Mmp3 mRNA levels were significantly elevated in the DKO ilea compared with the non-DKO controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several matrix metalloproteinase (Mmp), such as Mmp-2, -3 and -9 are up-regulated in the intestines of IBD patients and may regulate epithelial barrier function [45], [46]. Because the expression of these Mmps are associated with Nox1 and Duox1 [47], [48], [49], we analyzed the gene expression in our mice and found that Mmp-2 and Mmp-9 , but not Mmp3 mRNA levels were significantly elevated in the DKO ilea compared with the non-DKO controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that Duox2 and Nox1 have compensatory activities with overlapping functions to defend against bacterial invasion. Some of the oxidase effects are mediated through activation of Mmp proteins, and activation of Mmp-2 can maintain epithelial barrier function [46].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated matrix metalloproteinases (MMPs) respond as a pathogen in several diseases including arthritis, colorectal cancer, and IBD (O'Sullivan, Gilmer, & Medina, 2015). Nighot et al (2015) reported the upregulation of MMP-9 protein expression during chemically induced experimental colitis but not in the normal colonic mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The MMP-9 mucosal expression and protein levels, as well as serum antigen levels, were significantly higher in UC patients compared to controls, but MMP-9 does not seem to contribute to the severity of the disease. Meanwhile, MMP-2 has shown to be upregulated in pediatric CD [34]. The recently described roles for MMP-9 in IBD include VEGF-A processing, chemokine expression, neutrophil infiltration, generation of antiangiogenic factors, decreased goblet cell differentiation, and prevention of fibrosis [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%